2000
DOI: 10.1177/1359104500005001008
|View full text |Cite
|
Sign up to set email alerts
|

Can Post-Traumatic Stress Disorder be Diagnosed in Adolescence without a Catastrophic Stressor? A Case Report

Abstract: This article describes an adolescent girl who, having experienced repeated emotional bullying at school, developed a psychological disorder. The case is discussed in relation to current views on traumatic events and subsequent disorders. It is suggested that the diagnostic criteria for post-traumatic stress disorder may need to be modified to include cases where the precipitating event is less than catastrophic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
9
1
2
Order By: Relevance
“…More specifically, victimization tended to be associated with greater post-traumatic stress. Furthermore, as expected, bullying was associated with intrusive thoughts, as reported in the case study by Weaver (2000). However, we found no gender-linked differences, unlike earlier studies where girls were shown to be more severely affected than boys (Shannon, Lonigan, Finch, & Taylor, 1994).…”
Section: Discussion Of Studycontrasting
confidence: 56%
“…More specifically, victimization tended to be associated with greater post-traumatic stress. Furthermore, as expected, bullying was associated with intrusive thoughts, as reported in the case study by Weaver (2000). However, we found no gender-linked differences, unlike earlier studies where girls were shown to be more severely affected than boys (Shannon, Lonigan, Finch, & Taylor, 1994).…”
Section: Discussion Of Studycontrasting
confidence: 56%
“…Schools and institutions are likely to take bullying more seriously, and further studies of preventive and therapeutic programs are implemented to reduce bullying symptoms. Moreover, bullying victims may receive the appropriate treatment (Weaver, ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though there has been discussion whether exposure to bullying complies with the classification of trauma required for diagnosis of Posttraumatic Stress Disorder (PTSD) as defined within the DSM-IV-TR (APA 2000), practitioners often report PTSD symptoms in victims of bullying (Scott and Stradling 1992;Weaver 2000). Research focusing on workplace bullying has established a relationship with PTSD symptoms that appears to be quite strong (Björkqvist et al 1994;Leymann and Gustafsson 1996;Matthiesen and Einarsen 2004;Mikkelsen and Einarsen 2002).…”
mentioning
confidence: 98%